2019
DOI: 10.1016/j.ijid.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

First description of agonist and antagonist IP-10 in urine of patients with active TB

Abstract: We showed for the first time that agonist/antagonist IP-10 forms are measurable in urine. IP-10 levels associate with TB and pneumonia disease, suggesting their association with acute inflammation. Further studies are needed to assess their role to monitor TB treatment efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Furthermore, IP-10 could monitor anti-TB treatment responses and improve TB diagnosis with HIV 28 . A new form (agonist/antagonist) of IP-10 could be detected in TB patients, and it may help IP-10 in TB diagnosis 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IP-10 could monitor anti-TB treatment responses and improve TB diagnosis with HIV 28 . A new form (agonist/antagonist) of IP-10 could be detected in TB patients, and it may help IP-10 in TB diagnosis 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The detection of CXCL10 in urine using ELISA (Quanterix) has a sensitivity of 78% and a specificity of 94%. 22 The detection of the CXCL10 gene in serum has a sensitivity of 87.5% and a specificity of 78.9%. 21 Another study reveals that detection of CXCL10 in serum showed positive results in 87.5% of active pulmonary TB patients, 45.5% of latent TB, and 9.5% in control variables.…”
Section: Discussionmentioning
confidence: 99%
“…The study from Petrone et al in 2019. 22 was conducted using ELISA (Quanterix) to measure CXCL10 in urine, while this research was using PCR. Studies by Nonghanphithak et al in 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of IP-10 are found in blood, plasma or urine in infections such as HIV 35,36 , hepatitis C 3740 , bacteremia 41,42 and TB 4350 . It has recently been demonstrated that IP-10 secretion during TB disease originates from infected macrophages and multinucleated giant cells located in the granulomas, and early inactivation of the secreted chemokine by antagonist form of IP-10 which binds to CXCR3 but does not induce signalling, may also play a role in the pathogenesis of TB 51,52 . Several studies show that IP-10 declines during efficient treatment of many diseases including TB 25,38,42,53,54 .…”
Section: Discussionmentioning
confidence: 99%